Design, synthesis and biological evaluation of paralleled Aza resveratrol–chalcone compounds as potential anti-inflammatory agents for the treatment of acute lung injury. Issue 15 (1st August 2015) - Chen, Wenbo; Ge, Xiangting; Xu, Fengli; Zhang, Yali; Liu, Zhiguo; Pan, Jialing; Song, Jiao; Dai, Yuanrong; Zhou, Jianmin; Feng, Jianpeng; Liang, Guang
Graphical abstract: Paralleled Aza resveratrol–chalcone compounds were synthesized and evaluated for anti-inflammatory activities in the treatment of ALI. Abstract: Acute lung injury (ALI) is a major cause of acute respiratory failure in critically-ill patients. It has been reported that both resveratrol and chalcone derivatives could ameliorate lung injury induced by inflammation. A series of paralleled Aza resveratrol–chalcone compounds (5a –5m, 6a –6i ) were designed, synthesized and screened for anti-inflammatory activity. A majority showed potent inhibition on the IL-6 and TNF-α expression-stimulated by LPS in macrophages, of which compound6b is the most potent analog by inhibition of LPS-induced IL-6 release in a dose-dependent manner. Moreover, 6b exhibited protection against LPS-induced acute lung injury in vivo. These results offer further insight into the use of Aza resveratrol–chalcone compounds for the treatment of inflammatory diseases, and the use of compound6b as a lead compound for the development of anti-ALI agents.